A very fast 3-hydroxy-coumarin-based fluorescent probe for highly selective and sensitive detection of thiophenols and its application in water samples. Issue 38 (13th September 2016) - Wang, Xiao-Bo; Zhou, Jianhua; Zhang, Datong; Wang, Bin
Abstract : In this work, we have developed a novel off–on fluorescent probe by combining 7-diethylamino-3-hydroxy-coumarin as the fluorophore and 2, 4-dinitrobenzenesulfonate as the recognition unit. Abstract : In this work, we have developed a novel off–on fluorescent probe by combining 7-diethylamino-3-hydroxy-coumarin as the fluorophore and 2, 4-dinitrobenzenesulfonate as the recognition unit. This probe features a remarkable large Stokes shift (113 nm) and shows a highly selective and sensitive detection process for thiophenols with significant fluorescence turn-on responses. Biothiols, aliphatic thiols and reducing anions do not interfere with the sensing of thiophenols. Notably, it rapidly responds to various concentrations of PhSH and the fluorescence intensity reaches a plateau instantly. The limit of detection of the probe was found to be 7.3 nM in HEPES buffer (10 mM, pH 7.4) containing 30% THF as a co-solvent. The potential application of the probe was demonstrated by the quantitative detection of thiophenols in real water samples.